The study of ¹⁷⁷mLu decay - Lashko, A.P.; Lashko, T.N. (Вопросы атомной науки и техники, 2013)
High-precision measurements of the relative γ-ray intensities from the decay of ¹⁷⁷mLu were performed by means of a γ-spectrometer. The data were used to determine the internal conversion coefficient (ICC) for the K-forbidden E1-transition with the energy of 55 keV in ¹⁷⁷Hf. High value of the hindrance factor for the γ-radiation leads to anomalies in the ICC which are observed in the experiment. The discrepancy between experimental and theoretical values of ICC cannot be explained by admixtures of different multipolarities with the same parity. Such variance can be eliminated only by assuming the presence of intranuclear conversion.